2005
DOI: 10.1111/j.1365-2249.2005.02825.x
|View full text |Cite
|
Sign up to set email alerts
|

Diminished cytokine signalling against bacterial components in mononuclear leucocytes from ulcerative colitis patients after leukocytapheresis

Abstract: SummaryInfiltration by circulating inflammatory cells is a prominent local inflammatory feature of ulcerative colitis (UC). Several trials have suggested that leukocytapheresis by filtration can benefit patients with active UC. We investigated how this therapy might modulate the inflammatory response. Patients with active UC who were beginning repeated filtration leukocytapheresis were studied. Mononuclear cell preparations were obtained from blood before and after the first treatment, and expression of cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…[21][22][23] Furthermore, patients who develop pouchitis show higher activation of signal transducer and activator of transcription (STAT)-1, a transcription factor that activates genes involved in infl ammatory and immune responses, in the pouch mucosa. 24 LCAP may reduce infl ammation via the removal of activated leukocytes that produce infl ammatory cytokines such as interleukin (IL)-1, IL-6, and TNF-α, [25][26][27] and the removal of activated platelets that can produce active oxygen. [28][29][30] Standard medical therapy for pouchitis attempts to interfere with luminal bacteria using antibiotics or probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Furthermore, patients who develop pouchitis show higher activation of signal transducer and activator of transcription (STAT)-1, a transcription factor that activates genes involved in infl ammatory and immune responses, in the pouch mucosa. 24 LCAP may reduce infl ammation via the removal of activated leukocytes that produce infl ammatory cytokines such as interleukin (IL)-1, IL-6, and TNF-α, [25][26][27] and the removal of activated platelets that can produce active oxygen. [28][29][30] Standard medical therapy for pouchitis attempts to interfere with luminal bacteria using antibiotics or probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Additional mechanisms including the triggering of immunomodulatory or regulatory processes have been suggested to be operative [3,4,[15][16][17][18]. Moreover, the release of biologically active substances from the cells adsorbed in the apheresis columns has also been described [19,20].…”
Section: Introductionmentioning
confidence: 98%
“…We chose to analyze the following immunoregulatory markers, which could be adsorbed or released in the lines or in the apheresis filter (column): CD30L (regulatory ligand with described importance for IBD [24]), IL-1receptor-antagonist (earlier reported to be released in Adacolumn [16]) and LL-37 (an antimicrobial and regulatory peptide mainly contained in granulocytes [25,26]). …”
Section: Introductionmentioning
confidence: 99%
“…LCAP also blocked mononuclear cell activity, as assessed by proliferative responses and inflammatory cytokine production. In patients with UC, we previously found that LCAP inhibited cytokine production in LPS-stimulated PBMCs through reducing toll-like receptor-4 expression and the subsequent activation of NF-jB and mitogen-activated protein kinases [21]. LCAP also reduces cytokine-induced production of inflammatory cytokines from PBMCs [22].…”
Section: Discussionmentioning
confidence: 96%